Signal processing and stimulation potential within the ascending auditory pathway: a review - Quimby, Alexandra E.; Wei, Kimberly; Adewole, Dayo; Eliades, Steven; Cullen, D. Kacy; Brant, Jason A. (Frontiers in Neuroscience, 2023)
The human auditory system encodes sound with a high degree of temporal and spectral resolution. When hearing fails, existing neuroprosthetics such as cochlear implants may partially restore hearing through stimulation of auditory neurons at the level of the cochlea, though not without limitations inherent to electrical stimulation. Novel approaches to hearing restoration, such as optogenetics, offer the potential of improved performance. We review signal processing in the ascending auditory pathway and the current state of conventional and emerging neural stimulation strategies at various levels of the auditory system.